Bertie's guide to life and mothers : a 44 Scotland Street novel - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series., 2015)
"Newlywed painter and sometime somnambulist Angus Lordie might be sleepwalking his way into trouble with Animal Welfare when he lets his dog Cyril drink a bit too much lager at the local bar. The longsuffering Bertie, on the cusp of his seventh birthday party, has taken to dreaming about his eighteenth, a time when he will be able to avoid the indignity of unwanted girl attendees and the looming threat of a gender-neutral doll from his domineering mother Irene"--